Proposição e avaliação de técnicas alternativas para detecção de faltas de alta impedância - Grimaldi, Reginaldo Barnabé Gonzalez (2020)
In many situations, conductor rupture in distribution systems or even their contact with structures external to the systems (such as trees) does not sensitize protection systems. This type of occurrence and its variations are typically called high impedance faults. Considering the high severity of the problem by the concessionaires, the problem of high impedance faults can cause a series of material and immaterial damages, such as fines, administrative penalties, accidents and deaths. The present work has the objective of presenting three methodologies little explored in the literature for the detection of high impedance faults based on: Spectral Sub-band Centroid Energy Vectors, Teager Energy Operator and Linear Predictor Linear. Concerning validation of the methods, a database was created through simulations performed in the Alternative Transients Program, based on a real energy distribution system. In addition to high impedance faults, load energization and capacitor bank switching situations were also simulated in order to test the robustness of the method against probable false positives. A database containing real high impedance oscillographs was also used. From obtained results, a decision criterion was developed for each method aiming at the detection of high impedance faults based on the current signals through time. All three methods obtained success rates above 90%.